Apoplastic Cell Death-Inducing Proteins of Filamentous Plant Pathogens: Roles in Plant-Pathogen Interactions - Li, Ya; Han, Yijuan; Qu, Mengyu; Chen, Jia; Chen, Xiaofeng; Geng, Xueqing; Wang, Zonghua; Chen, Songbiao (Frontiers in Genetics, 2020)
Filamentous pathogens, such as phytopathogenic oomycetes and fungi, secrete a remarkable diversity of apoplastic effector proteins to facilitate infection, many of which are able to induce cell death in plants. Over the past decades, over 177 apoplastic cell death-inducing proteins (CDIPs) have been identified in filamentous oomycetes and fungi. An emerging number of studies have demonstrated the role of many apoplastic CDIPs as essential virulence factors. On the contrary, apoplastic CDIPs have been documented to be recognized by plant cells as pathogen-associated molecular patterns (PAMPs). The recent findings of extracellular recognition of apoplastic CDIPs by plant leucine-rich repeat-receptor-like proteins (LRR-RLPs) have greatly advanced our understanding of how plants detect them and mount a defense response. This review summarizes the latest advances in identifying apoplatic CDIPs of plant pathogenic oomycetes and fungi, and our current understanding of the dual roles of apoplastic CDIPs in plant-filamentous pathogen interactions.